2022
DOI: 10.1002/ptr.7458
|View full text |Cite
|
Sign up to set email alerts
|

Non‐psychotropic Cannabis sativa L. phytocomplex modulates microglial inflammatory response through CB2 receptors‐, endocannabinoids‐, and NF‐κB‐mediated signaling

Abstract: Cannabis sativa L. is increasingly emerging for its protective role in modulating neuroinflammation, a complex process orchestrated among others by microglia, the resident immune cells of the central nervous system. Phytocannabinoids, especially cannabidiol (CBD), terpenes, and other constituents trigger several upstream and downstream microglial intracellular pathways. Here, we investigated the molecular mechanisms of a CBD‐ and terpenes‐enriched C. sativa extract (CSE) in an in vitro model of neuroinflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 98 publications
2
18
0
Order By: Relevance
“…Given the peculiar ability of PFP in modulating cytokines release induced by a 24 h inflammatory stimulus, we investigated whether this effect could be associated with an early regulation of MAPKs activity by measuring the phosphorylation levels of JNK in HaCaT cells stimulated with LCTM for 60 min through the ELISA dosage. As previously described [ 20 ], JNK activation peaked at 60 min with a significant increase of about 2-fold compared to control cells (one-way ANOVA: p = 0.0022 vs. CTRL) ( Figure 6 ). Statistical analysis revealed that treatment with PFP, at the dose of 100 µg/mL, was effective in counteracting significantly the LCTM-induced increased levels of JNK phosphorylation after 60 min (post hoc: p = 0.0019 vs. LCTM) ( Figure 6 ).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Given the peculiar ability of PFP in modulating cytokines release induced by a 24 h inflammatory stimulus, we investigated whether this effect could be associated with an early regulation of MAPKs activity by measuring the phosphorylation levels of JNK in HaCaT cells stimulated with LCTM for 60 min through the ELISA dosage. As previously described [ 20 ], JNK activation peaked at 60 min with a significant increase of about 2-fold compared to control cells (one-way ANOVA: p = 0.0022 vs. CTRL) ( Figure 6 ). Statistical analysis revealed that treatment with PFP, at the dose of 100 µg/mL, was effective in counteracting significantly the LCTM-induced increased levels of JNK phosphorylation after 60 min (post hoc: p = 0.0019 vs. LCTM) ( Figure 6 ).…”
Section: Resultssupporting
confidence: 80%
“…Cell viability was tested using Cell Counting kit-8 (CCK-8, Merck KgaA, Germany) as previously described [ 20 ]. Briefly, HaCaT and HFF cells (5 × 10 4 ) were cultured in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of GIN, SHO, and ZTE were calculated by considering the percentage of each compound within the extract. Thus, the cells were pre-treated for 4 h with ZOE (10 μg/mL), GIN (1 μg/mL), SHO (0.17 µg/mL), and ZOE terpenoid-enriched fraction (ZTE, 3 µg/mL), and then stimulated with LPS (250 ng/mL) for 24 h [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…BCP–CB 2 R interactions prevent LPS-induced oligodendrocyte toxicity and microglia imbalance [ 98 , 99 ], as well as C6 glioma cell excitotoxicity [ 100 ]. Moreover, a standardized non-psychotropic C. sativa extract containing BCP displays significant activity in reducing pro-inflammatory cytokine synthesis in activated BV-2 microglia cells through CB 2 R signalling [ 101 ]. In an experimental model of autoimmune encephalomyelitis, BCP was described as regulating local and systemic immunity [ 102 ].…”
Section: β-Caryophyllenementioning
confidence: 99%